(untitled) (Research, Society and Development, 2025)
The aim of this article is to investigate the potential of Lego Braille Bricks as an innovative tool for bilingual English literacy among blind children in Early Childhood Education. The research employs a qualitative approach, integrating theoretical review, document analysis, and semi-structured interviews with Brazilian educators engaged in pioneering inclusion projects. The study discusses the impact of playfulness and assistive technology on students’ motivation, autonomy, and engagement, revealing positive outcomes in linguistic, cognitive, and socio-emotional development. It also identifies challenges such as teacher training, the lack of suitable bilingual materials, and structural limitations for widespread implementation in school contexts. Reinforcing the originality of the topic, the study proposes guidelines for inclusive pedagogical practices and values the creation of innovative strategies that inspire reflections on inclusion and meaningful learning. Contributing to scientific advancement, this article sensitizes for the need of truly accessible, broad, and humanized education, placing the learner at the core of meaningful learning and strengthening social ties.